Circulating inflammatory markers, cell-free mitochondrial DNA, cortisol, endocannabinoids, and N-acylethanolamines in female depressed outpatients. (2nd January 2023) - Behnke, Alexander; Gumpp, Anja Maria; Rojas, Roberto; Sänger, Timo; Lutz-Bonengel, Sabine; Moser, Dirk; Schelling, Gustav; Krumbholz, Aniko; Kolassa, Iris-Tatjana
Abstract: Objectives: Major depressive disorder (MDD) involves peripheral low-grade pro-inflammatory activity. This multi-biomarker case-control study characterises the proinflammatory status in MDD beyond C-reactive protein (CRP) and Interleukin (IL)-6 levels through investigating concomitant alterations of immunoregulatory biomolecules. Methods: In 20 female MDD patients and 24 non-depressed women, circulating levels of CRP, IL-6, cortisol, selected endocannabinoids (ECs; anandamide [AEA], 2-arachidonylglycerol [2-AG]), and N -acylethanolamines (NAEs), as well as circulating cell-free mitochondrial DNA (ccf-mtDNA) were measured. Results: We found higher serum CRP and plasma AEA levels in MDD and a positive association of CRP and AEA levels with current depressive symptoms. Blood levels of cortisol, ccf-mtDNA, 2-AG, and NAEs did depend on MDD diagnosis nor correlated with the severity of current depressive symptoms. CRP correlated positively with AEA, and AEA showed positive associations with 2-AG and NAE levels. Conclusions: In this study, female MDD outpatients with mild to moderate disorder severity did not substantially differ from non-depressed controls in the resting levels of multiple immunoregulatory markers in peripheral blood. Instead of investigating resting levels, future research on the role of inflammatory activity in MDD should focus on investigating the reactivity of pathways modulating the immune system upon exposure to physical and psychosocial stressors.